Atonía uterina asociada a expulsivo prolongado en mujeres de 15 a 35 años en Hospital Gustavo Domínguez - Santo Domingo de Los Tsachilas; enero-junio 2019. - Checa Vera, Jenniffer Lizeth (2020)
Uterine atony is generated when the uterus does not contract due to lack of tone, which causes the blood vessels to remain open and severe bleeding, that is, a loss of more than 1,000 milliliters of blood, that lack of tone prevents contraction after childbirth and a consequent delay in its involution after childbirth. Importantly, once the mother expels the baby and the placenta, an important process develops, which consists of a potent uterine contraction whose function is the closure of the blood vessels of the uterus, which allows the bleeding to be Minimum in the mother. But when this process does not occur, uterine atony or inertia originates and the result is a major hemorrhage and when not properly controlled it can have fatal consequences for the parturient, prevailing as one of the three main causes of maternal mortality in the world. And it is the second cause of death in Ecuador, with a frequency of 70%. The sample chosen in the present study were 28 patients of the Gustavo Domínguez Zambrano Hospital, treated in the January-June 2019 period, obtaining as a result that: the most frequent maternal complications of the prolonged expulsive period, is 50% uterine atony, for On the other hand, the age range in which this complication was mostly presented, was in the range of 15 to 20 years, with 36%, on the other hand the highest percentage with atony were the nulliparous pregnant women, who had hemorrhages with greater frequency in 55%, while those with prolonged expulsion periods were multiparous with 61%, on the other hand, patients who presented atony associated with prolonged expulsion were obtained a percentage of 70%, the largest number of cases being the highest risk factor that occurred in the prolonged period was the administration of uterotonics with 28%. It was also determined that only 61% of the professionals developed the correct management of the childbirth. Finally, it was concluded that uterine atony is associated with prolonged expulsion, determining as a solution to concurrent cases and its diminution, the realization of a program that seeks to train and raise awareness among health professionals in the correct management of the childbirth.